The Novel Gene VpPR4-1 from Vitis pseudoreticulata Increases Powdery Mildew Resistance in Transgenic Vitis vinifera L. - Dai, Lingmin; Wang, Dan; Xie, Xiaoqing; Zhang, Chaohong; Wang, Xiping; Xu, Yan; Wang, Yuejin; Zhang, Jianxia (Frontiers in Plant Science, 2016)
Pathogenesis-related proteins (PRs) can lead to increased resistance of the whole plant to pathogen attack. Here, we isolate and characterize a PR-4 protein from a wild Chinese grape Vitis pseudoreticulata which shows greatly elevated transcription following powdery mildew infection. Its expression profiles under a number of abiotic stresses were also investigated. The PR-4 gene was overexpressed in regenerated V. vinifera cv. Red Globe via Agrobacterium tumefaciens-mediated transformation and verified by the Western blot. The transgenic grapevines exhibited higher expression levels of PR-4 protein content than wild-type vines and also repressed the growth of powdery mildew. The PR gene responds differently to different stresses in the PR-4 transformants. This study demonstrates that PR-4 protein in grapes plays a vital role in defense against powdery mildew invasion.